017. Etiology of Acute Appendicitis in Paediatric Patients: A Literature Review - Alifian, Muhammad Farid; Yani, Ahmad (JBN (Jurnal Bedah Nasional), 2024)
Background : Appendicitis is a disease that can occur at any age. The incidence of appendicitis is 1.66 per 1000 children annually. 1-8% of patients who enter the paediatric emergency room with complaints of acute abdominal pain were acute appendicitis patients, and often requires surgery. The etiology and pathogenesis of appendicitis remains unclear despite the treatment of acute appendicitis is patent, some literature says that the etiology of appendicitis was multifactorial. Methods : A literature search was conducted using online database sites namely Cochrane, PubMed, EMBASE, and Proquest. Results : Literature searches on Cochrane, PubMed, EMBASE, and ProQuest database sites obtained 2,719 articles, 30 articles met the criteria. Among them, the etiology of acute appendicitis in paediatric patients was caused by obstruction of the appendiceal lumen because of appendiceal intraluminal fecalith, lymphoid hyperplasia, viral or bacterial infection, parasites, foreign bodies and tumors. Conclusion: The etiology of acute appendicitis in paediatric patients was caused by obstruction of the appendiceal lumen, most of the obstruction was caused by lymphoid hyperplasia whether accompanied by the presence of appendiceal intraluminal fecalith or not. Other etiologies such as obstruction due to parasites, foreign bodies and tumors.